Power, memory, architecture contested sites on India's Deccan Plateau, 1300-1600 - Eaton, Richard Maxwell; Wagoner, Phillip B. 1955- (New Delhi Oxford University Press, 2014)
Focusing on India's Deccan plateau in the turbulent sixteenth century, this book examines the political histories and material culture of fortified strongholds that were repeatedly contested by the region's rival primary centres. It explores the many ways that political power, monumental architecture, and collective memory interacted with one another. It also radically rethinks the usefulness of Hindu-Muslim relations as the master key for interpreting this period of South Asian history.
Keywords: Electronic books; Deccan (India) -- History -- To 1500.; Deccan (India) -- History -- 16th century